2004
DOI: 10.1023/b:pham.0000029294.70707.74
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for LHRH-Receptor Expression in Human Airway Epithelial (Calu-3) Cells and Its Role in the Transport of an LHRH Agonist

Abstract: Taken together, our results provide evidence that deslorelin is transported across the respiratory epithelium via the LHRH-receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Previous studies from our laboratory have used the AON approach to selectively reduce LHRH-R expression (29). Using this AON, previous studies have shown a decrease in the LHRH-R mRNA expression by ∼73 ± 10.2% and LHRH-R protein expression by 42 ± 4.8% in a lung cancer cell line (23). In this study, a decrease in cytotoxicity by the deslorelin-docetaxel conjugate was observed in both the LNCaP and PC-3 cells treated with AON against LHRH-R. Further, it was interesting to note that, although there is a significant decrease in cytotoxicity in the AON-treated group, the deslorelin-docetaxel conjugate is still significantly more cytotoxic compared with docetaxel alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our laboratory have used the AON approach to selectively reduce LHRH-R expression (29). Using this AON, previous studies have shown a decrease in the LHRH-R mRNA expression by ∼73 ± 10.2% and LHRH-R protein expression by 42 ± 4.8% in a lung cancer cell line (23). In this study, a decrease in cytotoxicity by the deslorelin-docetaxel conjugate was observed in both the LNCaP and PC-3 cells treated with AON against LHRH-R. Further, it was interesting to note that, although there is a significant decrease in cytotoxicity in the AON-treated group, the deslorelin-docetaxel conjugate is still significantly more cytotoxic compared with docetaxel alone.…”
Section: Discussionmentioning
confidence: 99%
“…Influence of Decreased LHRH-R Expression on the Efficacy of Deslorelin-Docetaxel Conjugate A previously described protocol was followed to determine the effect of decreased expression of LHRH-R on efficacy of deslorelin-docetaxel conjugate in vitro (23). Phosphorothioated antisense oligonucleotide (AON) and sense oligonucleotide (SON) directed against the LHRH-R, previously validated by Koushik et al (23) for reducing LHRH-R expression, were synthesized for this purpose (29).…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, our earlier investigations indicated that respiratory epithelial cells internalize deslorelin, a peptide agonist of luteinizing hormone releasing hormone (LHRH) receptor (Koushik et al, 2004). To enhance nanoparticle cell affinity and uptake in ocular tissues, we investigated the potential value of conjugating transferrin or deslorelin on nanoparticle surface (nanoparticle functionalization).…”
Section: Applications Of Nanotechnology For Back Of the Eye Diseasesmentioning
confidence: 99%
“…Deslorelin, a nonapeptide luteinizing hormone releasing hormone (LHRH) super-agonist has a molecular weight of 1285 Da and exerts its effects via the LHRH-receptor (LHRH-R) (8, 9). The LHRH-R, a member of the GPCR super family is expressed in various tissues including normal lung (10) and overexpressed on lung cancers cells (11, 12). We have established that deslorelin can be conjugated to docetaxel at the hydroxyl (-OH) group in the serine moiety (amino acid 4) via a glutarate linker (13).…”
Section: Introductionmentioning
confidence: 99%